(untitled) (Damascus University Journal of agriculture sciences, 2025)
The aim of the research is to study the economics of manufacturing apple jam and apricot jam, and its potential to improve the living conditions of the rural population in Sergaya, and it was achieved by estimating the total manufacturing costs and the economic returns achieved from manufacturing apple jam and apricot jam for the average agricultural season 2020/2021, in addition to counting The main problems related to its manufacture. To achieve its objectives, the research relied on a questionnaire form. Interviews were conducted with the respondents who manufacture apple and apricot jam in the study area, who were selected by a comprehensive survey method in the district of Sergaya and the affiliated villages. Their number reached about 85 farmers. The research relied on quantitative and economic analysis based on a number of economic indicators related to manufacturing costs and calculating The economic return, the added value and the net added value achieved from manufacturing jam in the study sample. The results of the analysis showed that the manufacture of apricot jam achieved a higher added value and net added value compared to the added value and net added value achieved by the manufacture of apples by double, and they also achieved good economic efficiency, meaning that the Syrian pound invested in the manufacture of apple jam returns to the product with a value of 0.254 Syrian pounds, while It returns with a value of 0.388 pounds in the case of manufacturing apricot jam, and the manufacture of apple and apricot jam achieved real economic feasibility in terms of all economic indicators, which was represented in the positive value of the net income indicator, and the employment rate that fell below the correct one, which indicates that the manufacture of apple and apricot jam in a sample The study is economically acceptable The research recommends the need for the concerned authorities to supervise and control the sales of manufactured products in order to prevent monopoly by traders and control prices, in order to protect producers, and in order to encourage them to manufacture so that it becomes one of the main sources of income.